Hematological and biochemical markers after a Brazilian Jiu-Jitsu tournament in world-class athletes - Brandao, F.; Fernandes, H. M.; Vilaca Alves, J.; Fonseca, S.; Machado Reis, V. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2014)
The objectives of this study were to assess the effect of participation in a Brazilian Jiu-Jitsu (BJJ) competition on biochemical and hematological markers, and to determine whether the skill level of the athletes influenced these responses. Thirty BJJ fighters were divided into two groups: an elite group (EL) including 20 subjects classified as 1stto 3rdplace in the previous World Championship, and a non-elite group (NEL) including 10 BJJ athletes not participating in competitions. A BJJ tournament was simulated using the same rules as those of the World Championship. Each athlete performed five fights of up to 10 minutes each, with 5-minute resting intervals between fights. The fighting order was random and fights confronted athletes of the same group. Pre- and post-competition blood samples were collected to assess biochemical and hematological markers. Participation in the competition induced significant increases in the following variables in athletes of the two groups: glucose, uric acid, urea, creatinine, total protein, albumin, creatine kinase, leukocytes, neutrophils, rods, and monocytes. There was a significant increase in platelet count only in the NEL group. Total protein and mean platelet volume were higher in athletes of the EL group, whereas eosinophil and monocyte numbers were higher in the NEL group. A significant time x group interaction was only observed for serum creatinine, with higher mean values in the EL group pre- and post-competition.